PENERAPAN METODE DISCOVERY LEARNING SEBAGAI CARA MENINGKATKAN KEAKTIVAN SISWA UNTUK MENEMUKAN RUMUS SUDUT RANGKAP MATERI TRIGONOMETRI - Kusumastuti, Nusandari (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2022)
The discovery learning method is a teaching method that regulates teaching so that children acquire knowledge that was previously unknown and not through notification, partially or wholly discovered by themselves. At SMAN 1 Kota Sorong, students' learning activity in class was very lacking. This study used the role model method, where the model used was the learning observed in SMA Negeri 1 Lawang to be adapted in SMA Negeri 1 Sorong City. The main objective of this role model research was to improve classroom learning practices that were used as objects at SMA Negeri 1 Sorong City by taking the model from SMA Negeri 1 Lawang. The research applied the discovery learning method by using the Student Activity Sheet to activate students in learning Trigonometry, especially the subject of Double Angles. Three main characteristics of discovery learning were carried out in research at SMAN 1 Sorong City, namely: (1) exploring and solving problems to create, combine and generalize knowledge; (2) student-centered; and (3) activities to combine new knowledge and existing knowledge. The application of the discovery method was proven to be able to make students of class XI IPA SMAN 1 Sorong City able to be actively involved in learning.